Market and value chain of chicken meat products in Bangladesh: A revolutionary impact on employment generation, enterprise development and food security - Amin, MR; Ali, MS; Rahman, KMM; Sarker, MSK; Sharmin, MF; Hashem, MA (Meat Research, 2024)
This study aims at assessing the revolutionary impact of chicken meat products on employment generation, enterprise development and livelihood improvement of people in Bangladesh through market and value chain analysis. Based on information from specialized meat companies, fast food shops, special restaurants and super markets through surveys, FGDs and KIIs it tries to assess revolutionary impact of chicken meat products on employment, income generation and consumers preference. Poultry sector contributes 37% of total meat production and about 22-27% of the total animal protein supply in the country. Fried chicken, chicken burger, chicken sandwich, chicken roll, chicken cutlet, chicken kebab, chicken samosa and chicken singara are very popular in fast food shops whereas chicken sandwich, chicken burger, chicken roll, crispy and spicy chicken fry are common in departmental stores. In restaurant, the most common items are grill chicken, chicken curry, chicken paratha, fried chicken, fried chicken wing, fried chicken drumsticks, chicken with cashew nut, sliced chicken with capsicum, sweet and sour chicken, fried boneless chicken, boneless chicken gravy, masala chicken curry and chicken chilli dry. The process of making variety of chicken products and branding are going on by different producers. Important chicken meat products available in the market are sausages, nuggets, meatballs, spring roll, samosa, singara, cutlet, kebab, burger, sandwich, sharma, lollipop, wonton, grilled chicken, and fried chicken. There are 28-30 Companies are producing frozen foods (Chicken). The markets of safe chicken meat products are gradually being expanded over the years. The market size of frozen food including meat products will be from BDT 10 to 12 thousand million. Several millions of trained people are engaged in the sector to produce and sell of chicken meats and earn a handsome amount of money and improve their livelihood. Value chain analysis shows that value of chicken meat products varies from BDT 517 to BDT 1800 for per kg boneless chicken meat at company level. These products may vary from BDT 620 to BDT 2160 restaurant level where they vary BDT 724 to BDT 2520 at fast food shop level for per kg boneless chicken meat.